Julius Caesar - Tree, Herbert Beerbohm, Sir, 1853-1917.; Shakespeare, William, 1564-1616.; His Majesty's Theatre (London, England); Theater Playbills and Programs Collection (Library of Congress); London Shakespeare Festival 1910 : London, England) (London : William Heinemann, 1904)
His Majesty's Theatre, proprietor and manager Sir Herbert Beerbohm Tree. London Shakespeare Festival (Sixth Year) 28th March to 30th April, 1910 "Julius Caesar." The overture, entr'acts and incidental music specially composed by Raymond Rose. Stage manager, Cecil King, associate stage manager Stanley Bell, musical director, Adolf Schmid, general manager, Henry Dana.
His Majesty's Theatre [London, England], Evening, Tuesday, April 12th [1910].
Title devised by Library staff.
Cast: William Haviland, Herbert Beerbohm Tree, Harry C. Hewitt, Lyn Harding, Henry Ainley, Edward Sass, C.H. Croker-King, Stuart Graham, Eric Ward, Frederick James, Jules Shaw, Hubert Carter, Frank Esmond, Shiel Barry, Henry Morrell, Clifford Heatherley, H. Smithson, Tom Boag, John Robertson, Carlton Rex, J.W. Braithwaite, Arthur Cleeve, W.B. Abingdon, Alfred Bellew, Miss Iris Hoey, Miss Elinor Foster, Miss Evelyn Millard.
"Third week's performances, April 11th to April 16th: Wednesday, April 13, Thursday, 14, Friday 15 (Evenings), 'Julius Caesar' ... Wednesday, April 13, (Afternoon), 'The Merchant of Venice' ...Thursday, April 14 (Afternoon), 'Hamlet' ... Saturday, April 16 (Afternoon), 'Hamlet' ... Saturday, April 16 (Evening) 'Twelfth Night' ..."
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: Theater programs -- England -- London; Theater programs -- 1910.